PENGARUH PRAKTIK KEWIRAUSAHAAN TERHADAP MOTIVASI BERWIRAUSAHA SISWA KELAS XII PEMASARAN DI SMKN 1 PONTIANAK - Marilin, Wahyuni Cici; Asriati, Nuraini; Genjik, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of entrepreneurial practice on the motivation of entrepreneurship students in Class XII Marketing at SMK 1 Pontianak. The form of research is correlation research and quantitative research forms. The sample technique used is saturated sampling. The sample in this study was class XII Marketing Department of SMK 1 Pontianak Academic Year 2018/2019 which amounted to 44 students. The sampling method is a descriptive method. Data was collected by questionnaires that had been tested for validity and reliability. This data uses the count of SPSS vol. 18 and Microsoft excel 2018. The results of this study indicate that after a simple linear regression test on variables X and Y it is said that the practice of entrepreneurship has a positive effect on the motivation of student entrepreneurship with the regression equation Y = 23,346 + 0,472 X and has an effect of 24,6%. By testing the hypothesis by comparing the significance value with 0.05 so that a significance value of 0.001 <0.05 was obtained so that it was concluded that (Ho) was rejected and (Ha) was accepted. Furthermore, comparing the value of t_count with ttable obtained by t_count 3.698> 1.680 t_table, it can be concluded that (Ho) is rejected and (Ha) is accepted which means there is an influence between